Faktor-Faktor yang Mempengaruhi Kegagalan IUD di Kota Yogyakarta Tahun 2013-2016 - Maranata, Maranata; Tyastuti, Siti; Hernayanti, Munica Rita (Jurnal Kesehatan Ibu dan Anak, 2017)
The highest in DIY for 2013-2016 in Jogja. The effects of the failure of IUD are abortus, sepsis, ectopic pregnancy, frequency of lowbirth and premature born. The factors that influence IUD failure are age, parity, IUD type, gynecology history (breast sickness,expulsion event). Uterus length, education, experience of using IUD, and the period in using IUD. This research purpose is to knowfactors that influence of IUD failure in Jogja from 2013-2016. This research is analytical observational with cross sectional design,simple random sampling technique. subject with 317 subject IUD acceptor. The selected variables are IUD's type, age, parity, periodof use expulsion IUD. Data collecting in this research is from IUD family planning report. Bivariate analysis showed that variablesaffecting IUD failure are IUD types (p=0,013), age (p=0.001), duration of used (p=0,000), expulsion (p=0,000). The resultsmultivariant collecting influence variable are IUD types (p=0.005) (PR 2.40, 95%, CI = 1.302 - 4.427), age (p=0.003) (PR=0.379 95%CI = 0.199-0.719), expulsion event (p=0.002) (PR = 3.677 95% CI = 1,591-8,498). Factors that influence IUD failure are IUD type,age, expulsion occurrence of parity and duration has no effect on IUD failure.